Variedades de la lengua española - Moreno Fernández, Francisco (Routledge, 2019)
"Variedades del Español presents an overview of dialectal and sociolinguistic variation in the Spanish speaking world from one of the leading experts in the field. By the end of the course the reader will be familiar with the features distinguishing different Spanish dialects, with an additional understanding of the historical and socio-political reasons and implications of these differences. Written in Spanish, the book will be of interest to both native and non-native Spanish speakers alike"--
Includes bibliographical references and index
Keywords: Electronic books; Sprachvariante; Spanisch